A contemporary understanding of nurses’ workplace social capital: A response to the rapid changes in the nursing workforce - Jiamin Xu (2020)
© 2019 The Authors. Journal of Nursing Management published by John Wiley & Sons Ltd. Aim: To provide an updated definition of the concept of nurses’ workplace social capital that addresses changes in the contemporary nursing workforce. Background: Social capital explains the components of a constructive work environment. Advancements in psychology of workplace and changes in the demographic structure of nursing workforce call for a revised version of nurses’ workplace social capital. Method: Walker and Avant's approach was implemented. Data were compiled from ‘Medline’ and ‘CINAHL’, ‘Google’ search engine, book chapters and expertise of nursing academicians. Results: Nurses’ workplace social capital is a relational network that is configured by interactions among healthcare professionals. Although, various attributes influence these interactions, Relational Network, Trust, Shared Understanding, Reciprocity and Social Cohesion are considered as the major attributes. A healthy relational network creates a healthy workplace which can be further fortified by effective communication, active group engagements and a supportive leadership. Conclusions: Results of our concept analysis should establish a theoretical groundwork for nurse leaders to better build and more effectively lead the contemporary nursing workforce. Implication for Nursing Management: Leaders’ dedication to workplace social capital is the tenet of a constructive workplace, which in return can support nurses to flourish in their clinical and the other professional responsibilities.